2016
DOI: 10.1152/jn.00017.2016
|View full text |Cite
|
Sign up to set email alerts
|

Relating normalization to neuronal populations across cortical areas

Abstract: Normalization, which divisively scales neuronal responses to multiple stimuli, is thought to underlie many sensory, motor, and cognitive processes. In every study where it has been investigated, neurons measured in the same brain area under identical conditions exhibit a range of normalization, ranging from suppression by nonpreferred stimuli (strong normalization) to additive responses to combinations of stimuli (no normalization). Normalization has been hypothesized to arise from interactions between neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 53 publications
7
61
1
Order By: Relevance
“…We therefore developed a simple leaky competing accumulator network model (Usher and McClelland, 2001) to test a new hypothesis of how these computations might be implemented. This model extends previous work to incorporate a known property of perceptual circuitry: tuned normalization Ruff et al, 2016;Verhoef and Maunsell, 2017), meaning each neuron is characterized by the specific degree to which it is normalized (i.e., inhibited) by surrounding network activity (Reynolds and Heeger, 2009;Carandini and Heeger, 2012), and specifically by units with opposing tuning preferences. We hypothesized that each neuron's degree of tuned normalization dictates how it differentially participates in discrimination decisions versus confidence judgments.…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…We therefore developed a simple leaky competing accumulator network model (Usher and McClelland, 2001) to test a new hypothesis of how these computations might be implemented. This model extends previous work to incorporate a known property of perceptual circuitry: tuned normalization Ruff et al, 2016;Verhoef and Maunsell, 2017), meaning each neuron is characterized by the specific degree to which it is normalized (i.e., inhibited) by surrounding network activity (Reynolds and Heeger, 2009;Carandini and Heeger, 2012), and specifically by units with opposing tuning preferences. We hypothesized that each neuron's degree of tuned normalization dictates how it differentially participates in discrimination decisions versus confidence judgments.…”
mentioning
confidence: 59%
“…Further, it was recently reported that neurons in primary sensory areas exhibit tuned normalization, i.e. that each neuron possesses a unique, consistent degree of normalization: some neurons are very sensitive to activity of other units in the network (especially those which have different tuning preferences), while others operate more independently Ruff et al, 2016;Verhoef and Maunsell, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations